Marginalisation of muslim writers in South Asian literature: Rokeya Sakhawat Hossain's English works - Hasan, Md. Mahmudul (SAGE Publications, 2012)
This article argues that there appears to be a pattern of disregarding the literary contributions of South Asian Muslim writers who produced English texts on a variety of topics. It then mainly contextualises Rokeya Sakhawat Hossain’s English works in the tradition of South Asian writing in English to identify a continuous trend of undervaluing Muslim literary contributions in English in the region. The article thus argues for a re-assessment of the evaluation of this literary tradition, so that the many forgotten South Asian Muslim writers in English, including Rokeya, regain their long overdue recognition.